A Systematic Review Investigating the Presence of Inflammatory Synovitis in Hip and Knee Joint Replacement Surgery. (18th October 2015) - Hosny, Sherif; Strambi, Francesco; Sofat, Nidhi; Field, Richard
Abstract : Synovial tissue can display an inflammatory response in the presence of OA. There is increasing interest to better understand the role of inflammation in OA, particularly with regard to those who require joint replacement. A systematic review of inflammatory synovitis in OA of literature databases was undertaken from their inception until October 14, 2014. Independent critical appraisal of each study was undertaken using the CASP appraisal tool. From a total of sixty-six identified citations, twenty-three studies were deemed eligible for review. The studies presented moderate to strong methodological quality. Strong correlation was identified between histological and imaging synovitis severity. Correlation was weaker between clinical symptoms and imaging and/or histological synovitis severity. There was little consensus, with regard to expressed cytokines and chemokines at the different stages of OA disease progression. Few studies investigated the influence of inflammatory synovitis on the outcome of major joint replacement. Research into inflammatory synovitis in OA is an emerging field. Longitudinal studies applying proven imaging modalities, histological analysis, and longer follow-up are required in order to further define our understanding of the role of synovitis in the pathogenesis of OA and its effects on outcomes following major joint replacement.